UNHCR Egypt's Impact on Refugees and Asylum Seekers: 2000-2020 - Bahar, Abdallah (AUC Knowledge Fountain, 2024)
This thesis examines the shifts in UNHCR Egypt’s practice and policy and their impacts on refugees and asylum seekers in Egypt. It focuses on procedures of reception, registration, refugee status determination (RSD), and resettlement. It also examines the changes in services provided to refugees and asylum seekers, such as health care, education, residency permits, and future change. In addition, the study explores the major reasons for these shifts and whether they are stimulated by the global refugee regime or other factors such as domestic legislation. The thesis attempts to answer the following two questions: 1) what are the shifts in UNHCR Egypt’s practice and policy that influences refugees and asylum seekers' situation in Egypt and why? 2) How does UNHCR Egypt's practice and policy shift affect the situation of refugees and asylum seekers? Structured interviews were conducted with 12 participants from UNHCR staff and partner organizations, academia, and community leaders of refugees and asylum seekers, as well as undertaking participant observation. The research findings show that despite some efforts by UNHCR to improve its policy and practice, it is working in an increasingly difficult context with constraints imposed by the government and the global refugee regime. The effects on the refugees and asylum seekers seem to be largely negative, with support declining and serious difficulties getting responses, delays in registrations, RSD interviews, and resettlement, and an inability to reach them on the phone or physically. Yet, there are a few positive changes, yet, some of them seem to be quite temporary or change to a negative impact after a short time, such as the change in residency permits. Keywords: UNHCR, practice, policy, shift, refugees, asylum seekers, registration, resettlement, protection